Percepción de las jugadoras internacionales de baloncesto sobre su toma de decisiones - Jimrnez Sanchez, A. C.; Saenz-Lopez Bunuel, P.; Ibanez Godoy, S. J.; Lorenzo Calvo, A. (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2012)
In sport science, there is a great interest of investigating the cognitive process of sportspeople. The main objective of this study is to analyse these decisions taken by high-level female players (Spanish national team) on the analysis of tactical attacking situations linked to 1on1 and 2 on 2. The sample of the research comprises of twelve female players chosen to make up the national team. The players will be interviewed about their decision-making in the competition and their performance in 1vs1 and 2vs2 situations. Female players know the importance of decision-making. There are differences between the guard players (point-guard, shooting-guard and small-forward) and the pivot players (power-forward and center) and we offer proposal training to improve the decision-making skills.